Socioeconomic transformation through the minimum basic needs approach: accomplishments, problems and research implications - Bautista, Victoria A. (1997)
A set of indicators called the minimum basic needs (MBN) constitutes the core strategy beging propagated under the Social Reform Agenda - a key program in the Ramos administration to address quality of life, sustainability and empowerment, particularly of the depressed, deprived and underserved sectors of the population. As of yearend 1995, nearly all local chief executives had been briefed on the MBN and trainors trained in almost all provinces and cities. By 1996, 24.6 percent of the 42,380 barangays in the country had already installed MBN. Common problems and issues encountered in the operationalization of MBN necessitate solutions and responses to ensure the viability of the approach. Nongovernment organizations (NGOs) and people's organization (POs) can take part in furthering the MBN technology by assuming the varied roles of partner, mobilizer, critic, policy advocate, or by engaging in self-reflection. - Reproduced
Keywords: Social reform